InSitμ@CHESS, a Resource for Studying Structural Materials. Issue 3 (4th May 2017) - Miller, Matthew P.; Obstalecki, Mark; Fontes, Ernest; Pagan, Darren C.; Ruff, Jacob P. C.; Beaudoin, Armand J.
Abstract : High-energy X-ray diffraction (HEXD) experiments, which include real-time measurements of micromechanical material response using in-situ loading and the non-destructive creation of three-dimensional maps of polycrystalline microstructure, are very rapidly replacing traditional macroscopic mechanical tests and forensic metallurgical characterization methods for structural materials. The center for Integrated Simulation and X-ray Interrogation Tools and Training for Micromechanics at the Cornell High Energy Synchrotron Source (InSitμ@CHESS) was created to facilitate the use of HEXD experiments on structural materials; more notably, metallic alloys such as steel, titanium, aluminum, and nickel. The Office of Naval Research (ONR) has financially supported InSitμ, specifically enabling enhanced industrial user support. This article describes the experimental considerations associated with using HEXD on structural materials and, through a set of examples, illustrates how InSitμ addresses these considerations.